Effect of Planting Method on the Growth of Alnus glutinosa and Quercus petraea in Compacted Opencast Coal‐Mine Spoils, South Wales. (11th February 2013) - Haigh, M.; Reed, H.; Flege, A.; D'Aucourt, M.; Plamping, K.; Cullis, M.; Woodruffe, P.; Sawyer, S.; Panhuis, W.; Wilding, G.; Farrugia, F.; Powell, S.
Abstract: Land degradation on officially 'reclaimed' opencast coal‐mine sites is a widespread problem in South Wales. This project explores methods suitable for use by community volunteers seeking to effect local environmental improvement by restoring geoecological self‐sustainability on lands that are commonly affected by extreme auto‐compaction and low soil nutrient status. This paper describes a formally established 7‐year experiment designed to assess the effect of three alternative tree planting strategies used in the forestation of such lands. These are notch planting (e.g. forestry), pit planting (e.g. parks and gardens) and trench planting (e.g. orchard terraces). The study explores tree survival and growth for two species commonly used in land reclamation contexts: alder [ Alnus glutinosa (L.) Gaertn] and Welsh or Durmast Oak [ Quercus petraea (Matt.) Liebl]. t ‐testing of the results shows that survival and growth rates for both species tend to be significantly better for trench planting than for pit planting than for notch planting. Differences in mortality between pit‐planted and trench‐planted trees become less significant during the experiment while differences in growth increase with time. The conclusion is that providing a loosened, lower density, rooting substrate significantly improves both the growth and the survival rates of trees planted in compacted Welsh surface coal‐mine spoils and that trench planting is more effective than parks and gardens‐style pit planting, which is more effective than forestry‐style notch planting. Copyright © 2013 John Wiley & Sons, Ltd.